2005
DOI: 10.1039/b512594d
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled synthesis of quantum-sized EuS nanoparticles and tuning of their Faraday rotation peak

Abstract: Size-controlled EuS nanoparticles were synthesized by the reaction of europium metal with thiourea as a sulfur source in liq. NH3, whose surface was confirmed to be modified with thiourea by FT-IR measurement, and the opto-magnetic properties (Faraday effect) of the EuS nanoparticles were investigated by using PMMA films containing the nanoparticles, showing that their Faraday rotation peaks were adjustable by control of their particle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…These magneto-optical properties are strongly dependent on their sizes [9]. Especially the photophysical properties of nano-sized materials are affected by size, shape, surface conditions and surrounding environment of the crystals [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These magneto-optical properties are strongly dependent on their sizes [9]. Especially the photophysical properties of nano-sized materials are affected by size, shape, surface conditions and surrounding environment of the crystals [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[14] During the past a few years, several research groups reported various routes to prepare the EuX NCs, such as with high temperature reduction, thermal or optical decomposition of single-source precursors, and a liquid-phase synthesis. [15][16][17][18] However these methods usually required special instruments and extra ligands for Eu 3+ , which were time-consuming with the product; meanwhile, the resulting EuX NCs exhibited poor optical and magnetic properties, with little potential in applications.…”
mentioning
confidence: 99%
“…[60] In fact, Yanagida et al earlier invented the liquid-phase synthesis of EuS NCs by the reaction of europium metal and H 2 S in liquid ammonia. [61] This reaction involves liquid ammonia (À78 8C), so the harsh conditions that were hard to control limited its wide use. Hence, the novel amine colloidal reduction approach invented by our group had the following advantages: [35] 1) the resulting NCs are highly disperse and shape-controlled; 2) no extra ligands are needed for the starting Eu 3 + , thus leading to few impurities in the resulting NCs with strong luminescence and magnetic properties; and 3) it is suitable for large-scale production with high synthetic reproducibility and easy handling.…”
Section: Synthesis Methodsmentioning
confidence: 99%